Quantifying quality of WEB site based on usability - JKR Sastry, Dr; Sreenidhi, N; Sasidhar, K (International Journal of Engineering and Technology, 2018)
Information dissemination is taking place these days heavily using web sites which are hosted on the internet. The effectiveness and effi-ciency of the design of the WEB site will have great effect on the way the content hosted on the WEB can be accessed. Quality of a web site, places a vital role in making available the required information to the end user with ease satisfying the users content requirements. A framework has been proposed comprising 42 quality metrics using which the quality of a web site can be measured. Howevercompu-tations procedures have not been stated in realistic terms.In this paper, computational procedures for measuring â€œusabilityâ€ of a WEB site can be measured which can be included into overall computation of the quality of a web site.